2007
DOI: 10.1634/stemcells.2007-0567
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Transplanted Green Fluorescent Protein+ Bone Marrow Cells into Adipose Tissue

Abstract: ABSTRACT؉ /CD29 ؉ . There was a significant difference in both the cell number and phenotype of the GFP ؉ ASCs in two different adipose compartments, the omental (abdominal) and the inguinal (subcutaneous) fat pads; a significantly higher number of GFP ؊ /CD90 ؉ cells were isolated from the subcutaneous depot as compared with the abdominal depot. The in vitro adipogenic differentiation of the ASCs was achieved; however, all cells that had differentiated were GFP ؊ . Based on phenotypical analysis, GFP ؉ cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…Therefore, bone-marrow-derived adipocytes may account in part for the detrimental changes in adipose metabolism and inflammation with aging and obesity (Majka et al, 2010). However, the significance of these findings has been questioned by others given that several studies did not observe a significant contribution of bone-marrow-derived progenitors to adipogenesis (Berry and Rodeheffer, 2013;Koh et al, 2007;Tomiyama et al, 2008).…”
Section: Endothelial Cellsmentioning
confidence: 97%
“…Therefore, bone-marrow-derived adipocytes may account in part for the detrimental changes in adipose metabolism and inflammation with aging and obesity (Majka et al, 2010). However, the significance of these findings has been questioned by others given that several studies did not observe a significant contribution of bone-marrow-derived progenitors to adipogenesis (Berry and Rodeheffer, 2013;Koh et al, 2007;Tomiyama et al, 2008).…”
Section: Endothelial Cellsmentioning
confidence: 97%
“…Instead, the GFP+ cells in WAT express macrophage markers, such as CD11b and CD45 ( 236 ). An independent study also showed that the majority of BM-derived GFP+ cells in WAT are CD45+, and that ASCs isolated from these WAT depots and differentiated into adipocytes in vitro do not express GFP ( 237 ). These fi ndings suggest that the donor BM-derived, multilocular cells that engraft in WAT are not bona fi de adipocytes.…”
Section: Ascs and Preadipocytes In Health And Diseasementioning
confidence: 99%
“…34 Thus, the highest infiltrations rates were observed in the gonadal WAT of female mice, occasionally reaching a maximum of »25%. In contrast, other studies have reported no significant contribution of BMDCs to either rat 35 or mouse 36 WAT, resulting in an uncertainty regarding over the role of BMDCs in murine adipogenesis.…”
mentioning
confidence: 86%